Nonsuicidal self-injury in a clinical sample of adolescents in Serbia - Kolundžija Ksenija; Srdanović-Maraš Jelena; Marković Jasminka; Dimić Tamara (Vojnosanitetski Pregled, 2023)
Background/Aim. Nonsuicidal self-injury (NSSI) among adolescents is recognized as a significant public health concern. Adolescents with mental health problems are at an especially high risk of NSSI. The aim of the study was to assess the sociodemographic and clinical characteristics of patients with NSSI and the features of NSSI, as well as the impact of emotional reactivity and internalizing/externalizing problems on them. Methods. The observational study included a clinical sample of 111 adolescents treated at the Department of Child and Adolescent Psychiatry, Psychiatric Clinic at the University Clinical Center of Vojvodina, from March 2018 to October 2019. The adolescents were divided into two groups: group A comprised of adolescents who had at least one episode of NSSI in the last year, and group B comprised of adolescents who had no NSSI episode in their experience. The following clinical scales were used to examine the differences between adolescents from group A and group B: self-report questionnaires about emotional and behavioral problems (Youth Self-Report – YSR, Child Behavior Checklist – CBCL), emotional reactivity (Emotion Reactivity Scale – ERS), and suicidality (Self- Injurious Thoughts and Behaviors Interview – SITBI). Results. Group A contained a total of 58 adolescents older than the subjects of group B and was predominated by female participants. They had the first episode of NSSI at 13.05 and the last at 14.80 years. The most common methods of NSSI were cutting, scratching, and biting. Adolescents from group A had higher scores on ERS, higher scores on internalizing and externalizing problems, as well as higher total scores on YSR, but there was no difference between groups regarding scores on the CBCL scale. Conclusion. Due to the results obtained for emotional and behavioral problems, adolescents with NSSI should have a detailed psychiatric assessment, including social support, pharmacotherapy, and psychotherapy, to better understand NSSI and help them develop better coping skills.